Precision Cutting of CVD-SiC Mold Inserts Using Polycrystalline Diamond Tool - Suzuki, Hirofumi; Furuki Tatsuya; Suzuki, Akihiro; Mirai, Sakaida; Fukuda Tatsuya (International journal of automation technology, 2025)
The demand for glass lenses for smartphones, digital cameras, automobile sensors, medical micro-endoscopes, and optical communication equipment has increased, and their optical performance requires further improvement. To fabricate aspherical mold inserts of chemical vapor deposition (CVD) for smartphones and automobile sensors precisely and efficiently, a new fabrication process using the developed polycrystalline diamond (PCD) tools was proposed and tested. In the experiments, the effects of CVD-silicon carbide (SiC) grain size on machined surface roughness were tested using the developed PCD tool, and the cutting force and specific machining energy were evaluated in comparison with the conventional grinding wheel. Finally, a hollowing PCD tool was produced to hollow the CVD-SiC plate. From the experiments, it is evident that the aspherical CVD-SiC mold inserts can be manufactured precisely and efficiently using the developed process.